Compressive strength development of concrete with modified cements - Rodríguez Rojas, Einer (2025)
This article presents the development curves of compressive strength through curing time for concrete mixtures made with three types of modified cements marketed in Costa Rica, and their combination with national aggregate from sources of pit and river. The cements used for the investigation were MM/A (E-C) – 28, MM/B (P-C) – 28 and MP A – AR, defined according to regulation RTCR 479:2015 Materiales de Construcción. Cementos Hidráulicos. Especificaciones. Due to the lack of resistance development curves for concrete made with different types of modified cements and aggregates commercialized in the country, the objective of this investigation was focused on obtaining such curves and the resistance development percentage. All the material used, was characterized according to the ASTM o INTECO standards procedures; it was also verified that the aggregates and cement to be used were adequate by the parameters established in ASTM C33/C33M-18 and INTE C147:2018, respectively. Cylindrical specimens of 150 mm x 300 mm were used to determinate the compressive resistance, being failed at 3, 7, 28 and 56 days; following a mix design determined from the ACI 211-91. A statistical analysis was performed to the generated data to establish relationships and support the results obtained. With this investigation it was possible to demonstrate that the cements commercialized in Costa Rica with a degree of blast furnace slag are able to present a significant resistance gain in the concrete after the 28 days of curing, the greater compressive resistance of the concrete is generated when using river aggregate, and generally the strength of the concrete does not vary significantly when using the same type of cement for different aggregates.